G254(P) Changing pattern of neonatal pda ligation across a network. (12th March 2018) - Chalia, M; Broster, S; Roy, R; Somisetty, S; Kelsall, AW
Abstract : Introduction: The management of the neonatal patent ductus arteriosus (PDA) remains controversial and subject to much debate. There is uncertainty about the type and timing of medical therapies. There are concerns about the long-term outcome after surgical ligation. Previous studies from our network suggested improved survival. 1 Subsequent work highlighted different referrals practices by the tertiary neonatal intensive care units (NICUs). The aim of this service evaluation was to review changing practice across this network over the last 18 years following a more standardised network approach of referral since 2013. Methods: Patients were identified from the Acute Neonatal Transport Service(ANTS) database. All infants requiring PDA ligation were transported by them to cardiac centres for surgical ligation between January 2004 and July 2017. Results: Over this period 252 neonates have been referred for PDA ligation. The numbers referred annually were a median of 15 (range 5–36), with a peak of 36 referrals in 2011. Most referrals (77%) were from the three tertiary NICUs. Prior to 2011 there was a clear difference in referral rates. Conclusions: A more standardised approach, where usually only infants who had failed extubation were referred for PDA ligation has resulted in a substantial reduction in the number of infants undergoing surgical closure. This reduction is not the result of a changing neonatal population nor a change in specific medical therapies to treat the PDA in any of the units. It almost certainly reflects more tolerance of a PDA alongside careful ventilation, fluid, and nutrition management. Reference: . Kang SL, et al. Cardiology in the Young 2013;(23):711–716.